Nuclear receptors : a practical approach - Picard, Didier (New York : Oxford University Press, 1999)
The steroid / nuclear receptor superfamily is a large and growing group of transcription factors that are studied by a large and varied number of basic and clinical researchers. The first two chapters describe the evolutionary biology of the superfamily and explain how to clone and characterize new receptors. Chapter 3 shows how to identify the ligands of novel receptors and chapter 4 explains the kinetic analysis of receptor interactions. In chapter 5, the reader is guided through the functional characterization of coactivators using microinjection. The next section covers receptor phosphorylation, ligand regulated transcription, and hormone resistance syndromes. Chapter 9 describes the in vitro assembly of Hsp90 complexes and chapter 10 explains yeast as a model system for looking at receptor function. The final chapter shows how heterologous proteins can be regulated by fusion to the hormone binding domain of a receptor. Nuclear Receptors: A Practical Approach is a comprehensive guide to studying members of the superfamily and will be invaluable to all researchers old and new.
Machine generated contents note: 1. Evolutionary biology of the nuclear receptor superfamily / M. Robinson / H. Escriva / V. Laudet -- 2. Initial characterization of new orphan receptors / R. Sladek / V. Giguere -- 3. Adopting orphans: finding ligands / W. Wahli / S. Kersten -- 4. Kinetic analysis of nuclear receptor interactions / L.P. Freedman / B.J. Cheskis -- 5. Functional characterization of co-activators using mammalian cell microinjection / T.-M. Mullen / M.G. Rosenfeld / [and others] / D.W. Rose -- 6. Analysis of steroid/nuclear receptor phosphorylation / N.L. Weigel / B.G. Rowan -- 7. Ligand- and cofactor-regulated transcription with chromatin templates / W.L. Kraus / J.T. Kadonaga -- 8. Hormone-resistance syndromes / M. Gurnell / V.K.K. Chatterjee -- 9. In vitro assembly of steroid receptor -- Hsp90 complexes / D.F. Smith -- 10. Yeast as a system for the study of nuclear receptor function / M.J. Garabedian / J.A. Iniguez-Lluhi / A. Kralli -- 11. Regulation of heterologous proteins by fusion to a hormone binding domain / D. Picard.
Includes bibliographical references and index.
Print version record.
eBooks on EBSCOhost
Keywords: Steroid hormones -- Receptors; Nuclear receptors (Biochemistry); Transcription factors; Receptors, Cytoplasmic and Nuclear; Transcription Factors; Receptors, Steroid; Hormones stéroïdes -- Récepteurs.; Récepteurs nucléaires (Biochimie); Facteurs de transcription; SOCIAL SCIENCE -- Anthropology -- Physical; Steroid hormones -- Receptors; Nuclear receptors (Biochemistry); Transcription factors; Receptors, Cytoplasmic and Nuclear; Receptors, Steroid; Nuclear receptors (Biochemistry); Steroid hormones -- Receptors; Transcription factors; Biochimie; Hormones stéroides -- Récepteurs.; Facteurs de transcription; Laboratory Manual; Laboratory manuals; Laboratory manuals; Manuels de laboratoire